Intraventricular synchronism assessment by gated-SPECT myocardial perfusion imaging in cardiac resynchronization therapy. Does cardiomyopathy type influence results? - Amalia Peix (EJNMMI Research, 2020)
Abstract Purpose To analyze the evolution post-cardiac resynchronization therapy (CRT) in left ventricular non-compaction (LVNC) cardiomyopathy (CM) patients compared to other types of CM, according to clinical and functional variables, by using gated-SPECT myocardial perfusion imaging (MPI). Methods Ninety-three patients (60 ± 11 years, 28% women) referred for pre-CRT assessment were studied and divided into three groups: 1 (non-ischemic CM with LVNC, 11 patients), 2 (ischemic CM, 28 patients), and 3 (non-ischemic CM, 53 patients). All were studied by a 99mTc-MIBI gated-SPECT MPI at rest pre-CRT implantation and 6 ± 1 months after, including intraventricular dyssynchrony assessment by phase analysis. Quality of life was measured by the Minnesota Living with Heart Failure Questionnaire (MLHFQ). Results No differences in sex, atherosclerotic risk factors other than smoking habit, and MLHFQ results were found among groups. LVNC CM patients were younger, with greater QRS width and lower left ventricular ejection fraction (LVEF) at baseline, but the differences were not significant. No significant differences were found at baseline regarding ventricular function, although end-systolic volume was slightly higher in LVNC CM patients. Mean SRS was significantly higher (p < 0.0001) in ischemic patients (14.9) versus non-ischemic ones (8.7 in group 1 and 9 in group 2). At baseline, LVNC CM patients were significantly more dyssynchronous: Their phase standard deviation (PSD) was higher (89.5° ± 14.2°) versus groups 2 (65.2° ± 23.3°) and 3 (69.7° ± 21.7°), p = 0.007. Although the quality of life significantly improved in all groups, non-ischemic patients (with or without LVNC) showed a higher LVEF increase and volumes reduction at 6 months post-CRT. Dyssynchrony reduced post-CRT in all groups. Nevertheless, those more dyssynchronous at baseline (LVNC CM) exhibited the most significant intraventricular synchronism improvement: PSD was reduced from 89.5° ± 14.2° at baseline to 63.7° ± 20.5° post-CRT (p = 0.028). Six months post-CRT, 89% of patients were responders: 11 (100%) of those with LVNC CM, 25 (86%) of those with ischemic CM, and 47 (89%) of patients with non-ischemic CM. No patient with LVNC CM had adverse events during the follow-up. Conclusion CRT contributes to a marked improvement in non-ischemic CM patients with non-compaction myocardium. Phase analysis in gated-SPECT MPI is a valuable tool to assess the response to CRT.